Static and Motional Feedthrough Capacitance of Flexural Microresonator - Wen-Teng Chang (Active and Passive Electronic Components, 2011)
The present paper evaluates the static and motional feedthrough capacitance of a silicon carbide-based flexural-mode microelectromechanical system resonator. The static feedthrough capacitance was measured by a network analyzer under atmospheric pressure. The motional feedthrough was obtained by introducing various values into the modeling circuit in order to fit the Bode plots measured under reduced pressure. The static feedthrough capacitance was 0.02 pF, whereas the motional feedthrough capacitance of an identical device was about 0.2 pF, which is one order of magnitude larger than the static feedthrough capacitance.